Eating disorders in athletes: A review of the literature - Cobb, K. L. (Hot topics in sports and athletics, 2008)
Athletes are at increased risk for eating disorders (ED). Eating disorders in athletes may have severe physical and mental consequences, including failure to attain peak bone mass, low-trauma fractures and stress fractures, vertebral instability and curvature, prolonged psychological difficulties with weight and food, and even death. The high prevalence and unique nature of ED in athletes have led researchers to describe athlete-specific syndromes, including anorexia athletica and the female athlete triad of disordered eating, menstrual irregularity, and osteopenia/osteoporosis. Eating disorders in athletes have distinct etiologies and require specialized approaches to diagnosis, prevention, and treatment. Research on ED in athletes has increased dramatically in the past two decades, following the rapid increase in women's participation in athletics; however, many gaps remain in our understanding. Participation in weight-dependent sports may also account for a considerable proportion of ED in men, but male athletes have not been well studied. This chapter will critically review the latest research on ED in athletes, including: (1) issues in the measurement of ED, including the female athlete triad; (2) sport-and gender-specific prevalences; (3) risk and protective factors; (4) short and long-term sequelae; (5) prevention strategies; and (6) treatment strategies, including a review of pharmacologic agents to prevent or treat osteopenia and osteoporosis. This chapter will identify gaps in the current research and recommend directions for future research.